2019
DOI: 10.1002/eem2.12025
|View full text |Cite
|
Sign up to set email alerts
|

Organic Templates for Inorganic Nanocrystal Growth

Abstract: Nanocrystals provide a variety of size and shape-dependent properties with applications in a wide range of areas, gaining much attention in the past few years. However, due to the nature of the kinetic nanocrystal growth, the procedures often require strict experimental conditions and the shape and size of nanocrystals are difficult to control. In such context, organic templates, which are artificially modified or synthesized, can direct inorganic nanocrystal nucleation and growth to achieve desired shape, siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 291 publications
(403 reference statements)
0
5
0
Order By: Relevance
“…In addition, additives like ligands and metal ions are required on many occasions. In recent years, it has been found that the organic template can guide the nucleation and growth of inorganic nanocrystals by artificial modification or synthesis to obtain the ideal shape, size, and final properties . Metal‐organic framework (MOF), a new type of porous crystalline material, is composed of two main components: inorganic vertices (metal ions or clusters) and organic linkers .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, additives like ligands and metal ions are required on many occasions. In recent years, it has been found that the organic template can guide the nucleation and growth of inorganic nanocrystals by artificial modification or synthesis to obtain the ideal shape, size, and final properties . Metal‐organic framework (MOF), a new type of porous crystalline material, is composed of two main components: inorganic vertices (metal ions or clusters) and organic linkers .…”
Section: Introductionmentioning
confidence: 99%
“…can act as the nanoscale templates to mediate the formation of biomimetic minerals; although in many cases these templates are formed by their spontaneous self-assembly. [587][588][589][590][591] Here we focus on the templates that do not self-assemble spontaneously to avoid overlaping with the previous content.…”
Section: Template-assisted Mineralizationmentioning
confidence: 99%
“…Dendrimers are monodisperse macromolecular structures with extending branches from the center, highly symmetrical and exhibit 3D or 0D morphology, which is essential for not only the formation but the stabilization of 0D nanostructures [45,46]. Generally, for metal nanocluster synthesis, metal ions are incorporated inside the dendrimer structure by coordinative interaction with functional groups of dendrimer interior.…”
Section: Dendrimer Templating For Nanostructure Formationmentioning
confidence: 99%